ANALISIS PENGARUH STOCK SELECTION SKILL DAN MARKET TIMING ABILITY DENGAN METODE TREYNOR-MAZUY DAN HENRIKSSON-MERTON TERHADAP KINERJA REKSA DANA SAHAM (Studi Pada Reksa Dana Saham Tahun 2010-2014) - Kireina, Intan Tiara; Sampurno, R. Djoko (Faculty of Economics and Business Diponegoro University, 2016)
There are some variety of investment instruments that exist as an alternative option for investors to invest their assets, one of it is a mutual fund. Mutual funds are a solution for the investors who have problems such as limited capital, information, capability and time to invest. This research conducted to examine the relationship between the performance of equity mutual fund with Sharpe’s measure with variables that affect it includes stock selection skill and market timing ability using two methods, which are Treynor-Mazuy method and Henriksson-Merton method. The data used in this research are monthly data on Net Asset Value (NAV), SBI and IHSG of 16 sample of equity mutual funds for 2010-2014. The reasearch shows that partially stock selection skill and market timing ability using the Treynor-Mazuy method have a significant positive impact to the performance of equity mutual fund. So as partially stock selection skill and market timing ability using the Henriksson-Merton method also have significant positive impact to the performance of equity mutual fund.